Effects of resistance training and nutritional support on osteosarcopenia in older, community-dwelling postmenopausal Korean females (ERTO-K study): a study protocol - Byung Chan Lee; Kyung Il Kim; Kang Hee Cho; Chang-Won Moon (BMC Geriatrics, 2024)
Abstract Background Osteosarcopenia is geriatric syndrome defined as the concomitant occurrence of osteopenia/osteoporosis, and sarcopenia. Osteosarcopenia is a relatively new concept in geriatric medicine; however, it may increase the risk of fragility fractures, several morbidities and mortalities, and socioeconomic costs. Although resistance exercises and nutritional support—including protein, calcium, and vitamin D—are potential non-pharmacological management procedures, evidence is still lacking. The objective of this study was therefore to evaluate the effect of combined resistance exercise and nutritional support on the quality and quantity of bone and muscle in postmenopausal females with osteosarcopenia. Methods This research proposal presents the protocol for a prospective, single-center, single-blinded, two-armed randomized controlled trial. Thirty-four participants with osteosarcopenia will be recruited and randomly divided into intervention and control groups; both groups will receive nutritional supplements (protein, 40 g; vitamin D, 1600 IU; calcium, 600 mg) daily. The intervention group will undergo 24 weeks of resistance exercise of increasing intensity, achieved through a three-phase step-up process. The primary outcomes will be the changes in skeletal muscle index and bone marrow density of the lumbar spine and femoral neck between the baseline and end of intervention (24 weeks). The secondary outcomes will be the body composition, whole body phase angle, physical function assessment, quality of life, psychological assessment, and bone turnover markers of participants, surveyed at multiple time points. Discussion This randomized controlled trial may reveal the effect of resistance exercise and nutritional support on older postmenopausal women with osteosarcopenia. The results will provide evidence for developing proper non-pharmacological management guidelines for postmenopausal women. Trial registration Clinical Research Information Service of Republic of Korea, KCT0008291, Registered on 16 March 2023, https://cris.nih.go.kr/cris/search/detailSearch.do/25262 .